Versatile Distributed Computing Taxonomy - Poovizhi, J. Mary Ramy (International Journal of Computer Sciences and Engineering, 2025)
As indicated by NIST meaning of distributed computing, it has five attributes: on-request self-benefit, broad network access, asset pooling, rapid elasticity, and measured services, while mobile computing figuring centers around gadget portability and setting mindfulness considering systems administration and versatile asset/information get to. Portable distributed computing is normally viewed as expanding on distributed computing and versatile registering; be that as it may, it has some one of a kind highlights, for example, benefit offloading, migration, composition Versatile distributed computing advances portable figuring innovations and use bound together flexible assets of fluctuated mists and system advances. This part gives a review of different vital ideas that are very identified with versatile distributed computing and outline their relations through genuine models.